Seal
By optimizing the 90° peeling adhesion and tear strength in the seal, ensuring the high water stopping property and roller adhesion effect of the seal in the water environment, the problems of difficulty in pasting seals and insufficient water stopping performance in the prior art are solved. .
Patent Information
- Application Number
- CN202380044880.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-17
- Filing Date
- 2023-06-02
- Publication Date
- 2025-01-14
AI Technical Summary
When existing seals are pressed and pasted with rollers and other components, the pasting effect is poor, and the water-stopping performance is not fully exerted, especially in water-contact environments, the sealing property is easily reduced.
A seal is designed that meets the conditions of F1≥F2, T>F2, F1≥0.3N/20mm, and F2≥0.3N/20mm, where F1 and F2 are 90° peeling adhesion and T is tearing Strength, through the balance of these forces, the seal is effectively pasted using rollers to ensure high water stop.
The seal is high in water-contact environment, and the adhesive process is smoother, avoiding the problem of adhesion between the seal and the roller, and improving the long-term use performance of the seal structure.
Smart Images

Figure CN119317685A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a sealing element. Background Art
[0002] Conventionally, seals that can fill gaps to exhibit water-stopping properties are known.
[0003] For example, Patent Document 1 describes a waterproof seal having a layer of a predetermined adhesive composition on at least one surface of a foam structure having closed cells. The layer contains a polymer having a predetermined polycarbonate structure.
[0004] In Patent Document 1, a water stop test is performed in a state where a sample of a water stop seal is sandwiched between two acrylic plates.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Laid-Open No. 10-77463 Summary of the invention
[0008] Problems to be solved by the invention
[0009] According to the description of Patent Document 1, it is not envisaged that the seal is attached while being pressed by a member such as a roller. The technology described in Patent Document 1 has room for further study from the viewpoint of such attachment and water-stopping properties.
[0010] Therefore, the present invention provides a seal which is advantageous from the viewpoint of bonding the seal while pressing the seal with a member such as a roller and from the viewpoint of water-stopping properties.
[0011] Solutions for solving problems
[0012] The present invention provides a seal, comprising: a first surface; and a second surface facing a direction opposite to the direction facing the first surface, wherein the seal satisfies the conditions of F1≥F2, T>F2, F1≥0.3N / 20mm, and F2≥0.3N / 20mm. In the conditions, F1 and F2 are respectively the 90° peeling adhesion [N / 20mm] measured by peeling off the first surface and the second surface in accordance with Japanese Industrial Standard (JIS) Z 0237:2022. In the conditions, T is the tear strength [N / 20mm] measured in accordance with JIS K 6252-1:2015 using a non-cut angular test piece made from a portion of the seal away from the first surface and the second surface.
[0013] Effects of the Invention
[0014] The above-mentioned seal is advantageous from the viewpoint of bonding the seal while pressing the seal with a member such as a roller and water-stopping properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 This is a cross-sectional view schematically showing an example of the sealing member of the present invention.
[0016] Figure 2 Yes means through Figure 1 The seal shown is a cross-sectional view of one example of a sealing structure provided.
[0017] Figure 3A It is schematically shown Figure 1 A cross-sectional view showing an example of a method of attaching a seal.
[0018] Figure 3B It is a cross-sectional view schematically showing an example of a method of attaching a seal material according to a reference example.
[0019] Figure 4 This is a diagram schematically showing another example of the method of attaching the sealing material of the present invention. DETAILED DESCRIPTION
[0020] Embodiments of the present invention will be described with reference to the accompanying drawings. It should be noted that the present invention is not limited to the following embodiments.
[0021] like Figure 1 As shown, the seal 1a has a first surface 11 and a second surface 12. The second surface 12 faces a direction opposite to the direction faced by the first surface 11. The seal 1a satisfies the conditions of F1≥F2, T>F2, F1≥0.3N / 20mm, and F2≥0.3N / 20mm. F1 is the 90° peeling adhesion [N / 20mm] measured by peeling off the first surface 11 in accordance with JIS Z 0237:2022. F2 is the 90° peeling adhesion [N / 20mm] measured by peeling off the second surface 12 in accordance with JIS Z 0237:2022. T is the tear strength [N / 20mm] measured in accordance with JIS K 6252-1:2015 using an uncut angular test piece made from a portion of the seal 1a away from the first surface 12 and the second surface 12. The uncut angled test piece for measuring the tear strength T may have dimensions different from those of the angled test piece described in JIS K 6252-1:2015 as long as the shape is similar to that of the angled test piece described in JIS K 6252-1:2015.
[0022] like Figure 2As shown, a sealing structure 2 can be provided using a sealing member 1a. The sealing structure 2 includes a sealing member 1a, a first component 3a, and a second component 3b. In the sealing structure 2, the sealing member 1a is arranged between the first component 3a and the second component 3b, and fills the gap between the first component 3a and the second component 3b. The first surface 11 contacts the first component 3a. The second surface 12 contacts the second component 3b. By satisfying the conditions of F1 ≥ 0.3N / 20mm and F2 ≥ 0.3N / 20mm for the sealing member 1a, in the sealing structure 2, the sealing property between the first surface 11 and the first component 3a is easily increased, and the sealing property between the second surface 12 and the second component 3b is easily increased. Therefore, even if the sealing structure 2 is used in an environment in contact with water, the sealing structure 2 is easy to exert high water stopping performance.
[0023] In order to obtain the sealing structure 2, for example, the sealing member 1a is glued to the first component 3a. Figure 3A As shown, the seal 1a can be pasted to the first member 3a using a roller 5. In a state where the seal 1a is arranged on the first member 3a in a manner that the first surface 11 contacts the first member 3a, the roller 5 can be made to roll on the second surface 12 while contacting the second surface 12, and the seal 1a is pasted on the first member 3a by pressing the seal 1a on the first member 3a by the roller 5. In the past, there have been almost no attempts to use a roller or other member to press and paste the surface of a seal having a specified adhesive force. The reason is that pressing the roller on the surface of a seal having a specified adhesive force and rolling the roller may cause the seal to be pasted on the roller, which can be imagined to be not an easy task. The inventors and others have repeatedly conducted in-depth research to achieve such pasting of the seal. After a large number of trial and error, it was found that in order to achieve such pasting, it is important that the specified 90° peeling adhesion and the specified tear strength of the seal meet the specified relationship.
[0024] like Figure 3A As shown, as the roller 5 rolls, a force f1 is generated between the first surface 11 and the first member 3a, and a force f2 is generated between the second surface 12 and the roller 5. In addition, a force t is generated toward the first surface 11 and the second surface 12 at a portion of the seal 1a away from the center of the first surface 11 and the second surface 12. The seal 1a satisfies the conditions of F1 ≥ F2 and T> F2, and these forces f1, f2, and t can be adjusted to a desired balance, so that the seal 1a can be attached to the first member 3a using the roller 5.
[0025] It is considered that force f1 is related to the 90° peeling adhesive force F1, and force f2 is related to the 90° peeling adhesive force F2. In addition, it is considered that the magnitude of force t that can prevent the seal 1a from tearing is related to the tear strength T. If the condition of F1≥F2 is satisfied, force f2 is prevented from becoming too large compared to force f1. Thus, the first surface 11 and the first member 3a are prevented from peeling off as the roller 5 rolls, and the seal 1a can be attached to the first member 3a. In addition, by satisfying the condition of T>F2, tearing in the center of the seal 1a due to the force t generated by the rolling of the roller 5 can be prevented. Therefore, even if the seal 1a is attached to the first member 3a by the roller 5, high water stopping performance can be exerted. It should be noted that the 90° peeling adhesive force measured in accordance with JIS Z 0237:2022 and the tear strength measured in accordance with JIS K6252-1:2015 were not originally compared. Therefore, it is usually not assumed that the seal is designed by comprehensively considering the 90° peeling adhesive forces F1 and F2 and the tear strength T.
[0026] Figure 3B An example of a method of attaching a seal 1x according to a reference example is schematically shown. The seal 1x includes a release liner 30, and the release liner 30 is arranged to cover the second surface 12x. Figure 3B As shown, in this pasting method, the roller 5 rolls on the release liner 30 while in contact with the release liner 30, and the seal 1x is pressed on the first member 3a by the roller 5. According to this pasting method, after the seal 1x is pasted on the first member 3a, the release liner 30 must be peeled off to expose the second surface 12x. Therefore, the operation for sealing between the first member 3a and the second member 3b tends to become complicated. On the other hand, according to the seal 1a, such an operation of peeling off the release liner can be omitted, and the sealing structure 2 can be obtained by a simple operation.
[0027] The seal 1a may be provided together with a release liner 30 that can be peeled off from the first surface 11 of the seal 1a. In this case, the release liner 30 is peeled off from the first surface 11 before the seal 1a is attached to the first member 3a using the roller 5, for example. Figure 4 As shown, the seal 1a and the release liner 30 can be provided as a roll 50, for example. In the roll 50, the seal 1a is pulled out while the release liner 30 is peeled off from the first surface 11 of the seal 1a, and the seal 1a is arranged on the first member 3a. Thereafter, the roller 5 is rolled on the second surface 12, and the seal 1a is attached to the first member 3a.
[0028] The 90° peel adhesion F1 and F2 are ideally 0.5N / 20mm or more, more ideally 0.8N / 20mm or more, and further ideally 1.0N / 20mm or more. The 90° peel adhesion F1 and F2 can be 2N / 20mm or more, 3N / 20mm or more, 4N / 20mm or more, or 5N / 20mm or more. The 90° peel adhesion F1 and F2 are, for example, 50N / 20mm or less. In this case, the material options for the seal 1a that meets the condition of T>F2 become more, and the manufacture of the seal 1a is not easily affected by the supply chain. The 90° peel adhesion F1 and F2 are ideally 35N / 20mm or less, more ideally 20N / 20mm or less, and further ideally 10N / 20mm or less.
[0029] The 90° peeling force F1 may be equal to the 90° peeling force F2, or may be greater than the 90° peeling force F2. As long as the ratio F1 / F2 of the 90° peeling force F1 to the 90° peeling force F2 satisfies the above conditions, it is not limited to a specific value. The ratio F1 / F2 may be, for example, 10 or less, 5 or less, 3 or less, or 2 or less.
[0030] As long as the condition of T>F2 is satisfied, the tear strength T is not limited to a specific value. The tear strength T is, for example, 5N / 20mm or more. Thus, for example, even if the distance between the first member 3a and the second member 3b in the sealing structure 2 changes due to vibration, it is not easy to tear inside the seal 1a, and the water-stopping property of the sealing structure 2 is easy to maintain for a long time. The tear strength T is ideally 10N / 20mm or more, and more ideally 30N / 20mm or more.
[0031] The tear strength T is, for example, 70 N / 20 mm or less. The tear strength T may be 60 N / 20 mm or less, or 50 N / 20 mm or less.
[0032] In seal 1a, 90° peel adhesion F1 一天 and F2 一天 Not limited to a specific value. F1 一天 The 90° peeling strength is measured in accordance with JIS Z0237:2022 by attaching the seal 1a to a test plate with the first surface 11 in contact, and then peeling off the seal 1a after one day. 一天 The 90° peeling strength F1 is measured in accordance with JIS Z 0237:2022 by attaching the seal 1a to a test plate with the second surface 12 in contact, and then peeling off the seal 1a after one day. 一天 and F2 一天For example, it is 5N / 20mm or more. In this case, for example, after only one day has passed since the sealing structure 2 was obtained using the sealing member 1a, the sealing structure 2 is likely to exhibit high water stopping properties. Therefore, even if the period from the completion of the sealing structure 2 to the actual application is short, the high water stopping properties will be exhibited, and thus the sealing member 1a has high added value.
[0033] 90° peel adhesion F1 一天 and F2 一天 The ideal value is 10N / 20mm or more, and the more ideal value is 15N / 20mm or more. 90° peeling strength F1 一天 and F2 一天 For example, it may be 120 N / 20 mm or less, or 100 N / 20 mm or less.
[0034] The viscosity value V of the second surface 12 is Tack Not limited to a specific value. Viscosity value V Tack For example, 20N / cm 2 Viscosity value V Tack It is determined by dividing the maximum value of the force acting on the probe when the end face of a probe having a circular end face with a diameter of 5 mm is pressed against the second face 12 with a force of 0.25 N for 1 second and then the probe is pulled away from the second face 12 at a speed of 100 mm / min by the area of the end face of the probe. Viscosity value V Tack For example, the viscosity value V can be measured using the measuring device and probe described in the examples. Tack 20N / cm 2 Next, when the seal 1 a is attached using the roller 5 , the roller 5 can be easily peeled off from the seal 1 a as the roller 5 rolls, and the attaching operation of the seal 1 a is facilitated.
[0035] Viscosity value V Tack Ideal is 18N / cm 2 Below, more preferably 16N / cm 2 Below, further preferably 14N / cm 2 Viscosity value V Tack For example, 0.1N / cm 2 above.
[0036] The distance between the first surface 11 and the second surface 12 is not limited to a specific value. This distance is, for example, 1 mm to 50 mm, 1 mm to 40 mm, 1 mm to 30 mm, 1 mm to 20 mm, or 2 mm to 20 mm.
[0037] In the seal 1a, the tensile modulus of the layer containing the second surface 12 or the portion with a thickness of 200 μm from the second surface 12 is not limited to a specific value. This tensile modulus is, for example, 2 MPa or more. Thus, when the seal 1a is pasted using the roller 5, as the roller 5 rolls, the roller 5 is easily peeled off from the seal 1a, and the pasting operation of the seal 1a becomes easy. This tensile modulus is ideally 2.5 MPa or more, and more ideally 3 MPa or more. This tensile modulus is, for example, 50 MPa or less, ideally 40 MPa or less, more ideally 30 MPa or less, and further ideally 25 MPa or less. The tensile modulus can be measured, for example, according to JIS K 6251:2017, according to the method described in the embodiment. A test piece can be made for peeling off the layer containing the second surface 12 in the seal 1a to measure the tensile modulus of the layer. The tensile modulus can be, for example, less than 2 MPa, and can be less than 1.5 MPa or less than 1.0 MPa. In this case, the tensile elastic modulus is, for example, 0.5 MPa or more.
[0038] like Figure 1 As shown, the sealing member 1a includes, for example, a foam 20. Thus, in the sealing structure 2, the sealing member 1a is easily compressively deformed in accordance with the gap between the first member 3a and the second member 3b, and the sealing structure 2 is easily provided with high water stopping properties.
[0039] The structure in the foam 20 is not limited to a specific structure. The foam 20 has, for example, a structure of independent bubbles. In this case, the liquid tightness inside the foam 20 is high, and the sealing structure 2 is easy to exert high water stopping properties. In addition, the tear strength T is easy to increase, and the pasting using the roller 5 can be made easier.
[0040] The foam 20 may have a semi-independent semi-continuous cell structure. In this case, the foam 20 includes continuous cells before compression deformation, and when the foam 20 is compressed to produce a compression deformation of 50% or more, the continuous portion is clogged and changes to the same structure as the independent cells.
[0041] The material forming the foam 20 is not limited to a specific material. The foam 20 is, for example, a rubber foam. The rubber foam is obtained by, for example, foaming a rubber composition containing rubber, a foaming agent, and a crosslinking agent.
[0042] Rubber can be, for example, an olefin elastomer, a styrene elastomer, a butyl elastomer, a vinyl chloride elastomer, or a natural rubber. Examples of olefin elastomers are ethylene-propylene rubber (EPM) and ethylene-propylene-diene rubber (EPDM). Styrene elastomers are styrene-butadiene rubber (SBR), styrene-butadiene-styrene rubber (SBS), styrene-isoprene-styrene rubber (SIS), styrene-ethylene-butadiene rubber, styrene-ethylene-butylene-styrene rubber (SEBS), styrene-isobutylene-styrene block rubber (SIBS), and styrene-isoprene-propylene-styrene rubber. Examples of butyl elastomers are butyl rubber, polyisobutylene rubber, polybutene, polyisoprene rubber, and nitrile rubber (NBR). Examples of vinyl chloride elastomers are chloroprene rubber and chlorosulfonated polyethylene rubber.
[0043] The rubber is preferably an olefin-based elastomer, more preferably EPDM. In this case, even when the compression deformation of the foam 20 in the sealing structure 2 is small, the sealing structure 2 can easily exhibit high water stopping properties.
[0044] EPDM is a rubber obtained by copolymerization of ethylene, propylene, and dienes. In addition to ethylene and propylene, dienes are copolymerized to introduce unsaturated bonds, and crosslinking with a crosslinking agent is possible.
[0045] Examples of dienes include 5-ethylidene-2-norbornene, 1,4-hexadiene, and dicyclopentadiene. These dienes can be used alone or in combination of two or more. When the dienes include dicyclopentadiene, an increase in the degree of crosslinking can be achieved.
[0046] EPDM preferably has long chain branches. The method of introducing long chain branches into EPDM is not limited to a specific method, and a known method can be adopted. If EPDM has long chain branches, the rubber composition can be foamed well.
[0047] The content of dienes in EPDM (diene content) is, for example, 1% by mass or more, preferably 2% by mass or more, and more preferably 3% by mass or more. The diene content is, for example, 20% by mass or less, and preferably 15% by mass or less. Thus, the rubber foam is not prone to surface shrinkage, and the rubber foam is not prone to cracking.
[0048] The foaming agent may be an organic foaming agent or an inorganic foaming agent.
[0049] Examples of organic foaming agents include azo foaming agents, N-nitroso foaming agents, hydrazide foaming agents, semicarbazide foaming agents, fluoroalkane foaming agents, triazole foaming agents, and other known organic foaming agents. Examples of azo foaming agents include azodicarbonamide (ADCA), barium azodicarboxylate, azobisisobutyronitrile (AIBN), azocyclohexanecarbonitrile, and azodiaminobenzene. Examples of N-nitroso foaming agents include N,N′-dinitrosopentamethylenetetramine (DTP), N,N′-dimethyl-N,N′-dinitrosoterephthalamide, and trinitrosotrimethyltriamine. Examples of hydrazide foaming agents include 4,4′-oxybis(benzenesulfonylhydrazide) (OBSH), p-toluenesulfonylhydrazide, diphenylsulfone-3,3′-disulfonylhydrazide, 2,4-toluenedisulfonylhydrazide, p,p-bis(benzenesulfonylhydrazide)ether, benzene-1,3-disulfonylhydrazide, and allylbis(sulfonylhydrazide). Examples of semicarbazide foaming agents include p-toluenesulfonylsemicarbazide and 4,4′-oxybis(benzenesulfonylsemicarbazide). Examples of fluoroalkane foaming agents include trichloromonofluoromethane and dichloromonofluoromethane. An example of a triazole foaming agent is 5-morpholinyl-1,2,3,4-thiatriazole. The organic foaming agent may be a heat-expandable microparticle formed by encapsulating a heat-expandable substance in a microcapsule. Examples of such heat-expandable microparticles include commercially available products such as Microsphere (trade name, manufactured by Matsumoto Oil & Fats Co., Ltd.).
[0050] Examples of inorganic foaming agents include bicarbonates, carbonates, nitrites, borohydrides, inorganic azides, and other known inorganic foaming agents. Examples of bicarbonates include sodium bicarbonate and ammonium bicarbonate. Examples of carbonates include sodium carbonate and ammonium carbonate. Examples of nitrites include sodium nitrite and ammonium nitrite. An example of borohydride is sodium borohydride. These foaming agents may be used alone or in combination of two or more.
[0051] The amount of the foaming agent is, for example, 0.1 parts by mass or more, preferably 1 parts by mass or more, more preferably 10 parts by mass or more, based on 100 parts by mass of the rubber, and is, for example, 50 parts by mass or less, preferably 30 parts by mass or less.
[0052] Examples of crosslinking agents include sulfur compounds such as sulfur (S8) and 4,4'-dithiodimorpholine, selenium, magnesium oxide, lead monoxide, quinone dioxime, dibenzoylquinone dioxime, quinone compounds such as poly-p-dinitrosobenzene, polyamines, nitroso compounds such as p-dinitrosobenzene, organic peroxides, resins, and ammonium salts such as ammonium benzoate. Examples of organic peroxides include diisopropylbenzene peroxide, dimethyldi(tert-butylperoxide)hexane, 1,1-di(tert-butylperoxide)cyclohexane, and α,α'-di(tert-butylperoxide)diisopropylbenzene. Examples of resins include alkylphenol-formaldehyde resins and melamine-formaldehyde condensates. These crosslinking agents may be used alone or in combination of two or more.
[0053] The crosslinking agent is preferably sulfur (S8) and a sulfur compound, a quinone compound, or an organic peroxide. Sulfur (S8) and sulfur compounds are advantageous from the viewpoint of excellent mechanical strength and foamability. Quinone compounds are advantageous from the viewpoint of reducing the sulfur atom content ratio, reducing corrosiveness, and excellent foamability. Organic peroxides are advantageous from the viewpoints of improving the adhesion and height difference tracking properties of the object used to realize the sealing structure.
[0054] The mixing ratio of the crosslinking agent is, for example, 0.05 parts by mass or more, preferably 0.5 parts by mass or more, and more preferably 1 part by mass or more, relative to 100 parts by mass of the rubber. The mixing ratio of the crosslinking agent is, for example, 30 parts by mass or less, preferably 20 parts by mass or less, and more preferably 10 parts by mass or less, relative to 100 parts by mass of the rubber.
[0055] As a cross-linking agent, a quinoid compound and an organic peroxide can be used in combination. In this case, it is easy to fully perform cross-linking at the surface of the foam 20. In the case of using a quinoid compound and an organic peroxide in combination, the mixing ratio of the organic peroxide is, for example, 1 part by mass or more, and more preferably 10 parts by mass or more, relative to 100 parts by mass of the quinoid compound. Its mixing ratio is, for example, 100 parts by mass or less, and preferably 50 parts by mass or less, relative to 100 parts by mass of the quinoid compound.
[0056] The rubber composition preferably contains a foaming aid and a crosslinking aid. Examples of the foaming aid are urea foaming aids, salicylic acid foaming aids, benzoic acid foaming aids, and metal oxides such as zinc oxide. Urea foaming aids and metal oxides are preferably listed. These foaming aids can be used alone or in combination of two or more.
[0057] The blending ratio of the foaming aid is, for example, 0.5 parts by mass or more, preferably 1 part by mass or more, and for example, 20 parts by mass or less, more preferably 10 parts by mass or less, per 100 parts by mass of the rubber.
[0058] Examples of crosslinking aids include thiazoles, thioureas, dithiocarbamic acids, guanidines, sulfenamides, thiurams, xanthates, aldehyde amines, and aldehyde amines. Among them, it is desirable to use thiazoles, thioureas, dithiocarbamic acids, or thiurams as crosslinking aids. Examples of thiazoles are dibenzothiazole disulfide and 2-mercaptobenzothiazole. Examples of thioureas are diethylthiourea, trimethylthiourea, and dibutylthiourea. Examples of dithiocarbamic acids are sodium dimethyldithiocarbamate, sodium diethyldithiocarbamate, zinc dimethyldithiocarbamate, zinc diethyldithiocarbamate, and zinc dibenzyldithiocarbamate. Examples of guanidines are diphenylguanidine and di-o-tolylguanidine. Examples of sulfenamides are benzothiazole-2-diethylsulfenamide and N-cyclohexyl-2-benzothiazolesulfenamide. Examples of thiurams are tetramethylthiuram monosulfide, tetramethylthiuram disulfide, and tetrabenzylthiuram disulfide. Examples of xanthates are sodium isopropyl xanthate and zinc isopropyl xanthate. Examples of aldehydeamines are acetaldehyde ammonia and hexamethylenetetramine. Examples of aldehydeamines are n-butylaldehyde aniline and butyraldehyde monobutylamine.
[0059] The cross-linking aid can be alcohols. Examples of alcohols are monohydric alcohols such as ethanol, dihydric alcohols such as ethylene glycol, trihydric alcohols such as glycerol, and polyols (polyoxyethylene glycol) such as polyethylene glycol and polypropylene glycol. As alcohols, it is desirable to use polyols. In this case, the number average molecular weight of the polyol is, for example, more than 200, and ideally more than 300. The number average molecular weight of the polyol is, for example, less than 10,000, and ideally less than 5,000.
[0060] These cross-linking aids may be used alone or in combination of two or more.
[0061] When sulfur and sulfur compounds are used as the crosslinking agent, from the viewpoint of ensuring a good foamed shape and flexibility of the foam 20 , it is desirable to use thiazoles, thioureas, dithiocarbamic acids, or thiurams as the crosslinking aid.
[0062] When a quinone compound is used as a crosslinking agent, it is desirable to use an alcohol as a crosslinking aid, and it is more desirable to use a polyol, from the viewpoint of reducing corrosivity. In particular, when a derivative of p-quinone dioxime is used as a quinone compound, it is advantageous to use polyethylene glycol. If polyethylene glycol is used as a polyol, the rubber composition can be well crosslinked, and excellent foaming properties can be easily ensured.
[0063] The mixing ratio of the crosslinking aid is, for example, 0.01 parts by mass or more, preferably 0.02 parts by mass or more, and more preferably 0.06 parts by mass or more, relative to 100 parts by mass of the rubber. The mixing amount is, for example, 20 parts by mass or less, preferably 10 parts by mass or less, and more preferably 5 parts by mass or less, relative to 100 parts by mass of the rubber.
[0064] The rubber composition may contain additives such as a lubricant (processing aid), a pigment, a filler, a flame retardant, and a softener as necessary.
[0065] Examples of lubricating materials include stearic acid, its esters, stearic compounds such as zinc stearate, and paraffin. These lubricating materials can be used alone or in combination of two or more lubricating materials. The mixing ratio of the lubricating material is, for example, 0.1 parts by mass or more, and preferably 1 part by mass or more, relative to 100 parts by mass of rubber. The mixing ratio is, for example, 20 parts by mass or less, and more preferably 10 parts by mass or less, relative to 100 parts by mass of rubber.
[0066] An example of a pigment is carbon black. The pigment may be used alone or in combination of two or more pigments. The mixing ratio of the pigment is, for example, 1 part by mass or more, and preferably 2 parts by mass or more, relative to 100 parts by mass of the rubber. The mixing ratio is, for example, 50 parts by mass or less, and preferably 30 parts by mass or less, relative to 100 parts by mass of the rubber.
[0067] The filling material can be an inorganic filling material, an organic filling material, or other known filling materials. Examples of inorganic filling materials are calcium carbonate, magnesium carbonate, silicic acid and its salts, clay, talc, mica powder, bentonite, silica, alumina, aluminum silicate, and aluminum powder. Examples of organic filling materials are cork. These filling materials can be used alone or in combination with two or more filling materials. The mixing ratio of the filling material is, for example, more than 10 parts by mass, ideally more than 30 parts by mass, and more ideally more than 50 parts by mass relative to 100 parts by mass of rubber. Its mixing ratio is, for example, less than 300 parts by mass, ideally less than 200 parts by mass relative to 100 parts by mass of rubber.
[0068] Examples of flame retardants are hydroxides such as calcium hydroxide, magnesium hydroxide, and aluminum hydroxide. These flame retardants can be used alone or in combination of two or more flame retardants. The flame retardant is present in an amount of, for example, 5 or more parts by mass, preferably 10 or more parts by mass, and more preferably 15 or more parts by mass relative to 100 parts by mass of rubber. The flame retardant is present in an amount of, for example, 200 or less parts by mass, preferably 150 or less parts by mass, and more preferably 100 or less parts by mass relative to 100 parts by mass of rubber.
[0069] Examples of softeners include petroleum oils, asphalts, low molecular weight polymers, organic acid esters, and tackifiers. Examples of petroleum oils include paraffin processing oils such as paraffin oil, cycloparaffin processing oils, drying oils or animal and vegetable oils, and aromatic processing oils. Examples of drying oils or animal and vegetable oils include linseed oil. Examples of organic acid esters include phthalates such as di-2-ethylhexyl phthalate (DOP) and dibutyl phthalate (DBP), phosphates, higher fatty acid esters, and alkyl sulfonates. As a softener, it is ideal to use petroleum oils or asphalts, and it is more ideal to use paraffin processing oils. These softeners can be used alone or in combination of two or more softeners. The blending ratio of the softener is, for example, 5 parts by mass or more, and ideally 10 parts by mass or more, relative to 100 parts by mass of rubber. Its blending ratio is, for example, 300 parts by mass or less, and more ideally 200 parts by mass or less, relative to 100 parts by mass of rubber.
[0070] The rubber composition may contain known additives such as a plasticizer, an antioxidant, an antioxidant, a colorant, a mildew preventer, and a non-rubber polymer, depending on the purpose and application.
[0071] like Figure 1 As shown, the sealant 1a may include at least two layers. This makes it easy to adjust F1, F2, and tear strength T so as to satisfy the conditions of F1≥F2, T>F2, F1≥0.3N / 20mm, and F2≥0.3N / 20mm. The sealant 1a may be composed of only one layer.
[0072] like Figure 1 As shown, the sealant 1a may, for example, include an adhesive layer 10 that forms at least one surface selected from a group consisting of a first surface 11 and a second surface 12. Thus, it is easy to adjust the peeling adhesion F1 and F2 to a desired range. In the sealing structure 1a, for example, the first surface 11 is formed by a first adhesive layer 10a, and the second surface 12 is formed by a second adhesive layer 10b. In other words, the sealant 1a includes a pair of adhesive layers 10 that form both the first surface 11 and the second surface 12. The sealant 1a may be changed to a layer other than the adhesive layer 10 to form the first surface 11. For example, the first surface 11 may be changed to a foam 20 to form the first surface 11. Alternatively, the sealant 1a may be changed to a layer other than the adhesive layer 10 to form the second surface 12. For example, the foam 20 may be changed to form the second surface 12.
[0073] As long as the conditions of F1 ≥ F2, T > F2, F1 ≥ 0.3 N / 20 mm, and F2 ≥ 0.3 N / 20 mm are satisfied, the adhesive layer 10 is not limited to a specific embodiment. Figure 1As shown, the adhesive layer 10 contains filler 10f, for example. For example, the second adhesive layer 10b contains filler 10f. In this case, the filler 10f may be present in a portion of the second surface 12. Thus, the viscosity value V of the second surface 12 Tack The first adhesive layer 10a may contain a filler.
[0074] The material of the filler 10f is not limited to a specific filler. The filler 10f includes, for example, an inorganic substance. Examples of the inorganic substance are calcium carbonate, magnesium carbonate, clay, talc, mica, bentonite, silica, alumina, aluminum silicate, and aluminum.
[0075] The adhesive layer 10 is formed as an adhesive layer, for example. The adhesive layer 10 contains, for example, a matrix 10m and a filler 10f. The filler 10f is dispersed in the matrix 10m. The matrix 10m contains, for example, a rubber polymer. The rubber polymer is, for example, a synthetic rubber such as a thermoplastic elastomer and a thermosetting elastomer. The adhesive layer 10 may not contain the filler 10f.
[0076] Examples of thermoplastic elastomers are olefin elastomers, styrene elastomers, butyl elastomers, and vinyl chloride elastomers. Examples of olefin elastomers are ethylene-propylene rubber (EPM) and ethylene-propylene-diene rubber (EPDM). Examples of styrene elastomers are styrene-butadiene rubber (SBR), styrene-butadiene-styrene rubber (SBS), styrene-isoprene-styrene rubber (SIS), styrene-ethylene-butadiene rubber, styrene-ethylene-butylene-styrene rubber (SEBS), styrene-isobutylene-styrene block rubber (SIBS), and styrene-isoprene-propylene-styrene rubber. Examples of butyl elastomers are butyl rubber, polyisobutylene rubber, polybutene, polyisoprene rubber, and nitrile rubber (NBR). Examples of vinyl chloride elastomers are chloroprene rubber or chlorosulfonated polyethylene rubber.
[0077] Examples of the thermosetting elastomer are silicone rubber, fluororubber, acrylic rubber, and polyamide rubber.
[0078] The rubber-based polymer is preferably a thermoplastic elastomer, more preferably a styrene-based elastomer or a butyl-based elastomer.
[0079] The weight average molecular weight of the rubber polymer is, for example, more than 30,000, preferably more than 50,000, and more preferably more than 100,000. The weight average molecular weight of the rubber polymer is, for example, less than 5,000,000, preferably less than 3,000,000, and more preferably less than 1,000,000. In this case, the face formed by the adhesive layer 10 easily has the desired adhesive force. The weight average molecular weight is measured using gel permeation chromatography in terms of polystyrene.
[0080] The content of the filler 10f in the adhesive layer 10 is not limited to a specific value. For example, in the adhesive layer 10, the content of the filler 10f is, for example, 5 parts by mass or more, preferably 10 parts by mass or more, and more preferably 20 parts by mass or more, relative to 100 parts by mass of the rubber-based polymer of the matrix 10m. The content of the filler 10f is, for example, 300 parts by mass or less, preferably 250 parts by mass or less, and more preferably 200 parts by mass or less, relative to 100 parts by mass of the rubber-based polymer of the matrix 10m.
[0081] The matrix 10m preferably further contains a tackifier. Thus, for example, the surface formed by the adhesive layer 10 is likely to have a desired adhesive force, and for example, the adhesive force of the surface formed by the adhesive layer 10 is likely to be high after a predetermined time has passed since the sealing structure 2 is obtained by the sealing member 1a.
[0082] The tackifier is not limited to a specific substance. The tackifier is, for example, a specified resin. Examples of this resin are rosin-based tackifier resins, terpene-based tackifier resins, hydrocarbon-based tackifier resins, phenol-based tackifier resins, ketone-based tackifier resins, polyamide-based tackifier resins, epoxy-based tackifier resins, and elastic-based tackifier resins. Examples of rosin-based tackifier resins are unmodified rosin, modified rosin, rosin phenol-based resins, and rosin ester-based resins. Examples of terpene-based tackifier resins are terpene-based resins, terpene-phenol-based resins, styrene-modified terpene-based resins, aromatic-modified terpene-based resins, and hydrogenated terpene-based resins. Examples of hydrocarbon-based tackifier resins are aliphatic hydrocarbon resins, aliphatic cyclic hydrocarbon resins, aromatic hydrocarbon resins, aliphatic / aromatic petroleum resins, aliphatic / alicyclic petroleum resins, hydrogenated hydrocarbon resins, coumarone resins, and coumarone indene resins. Examples of aromatic hydrocarbon resins are styrene resins and xylene resins. Examples of phenolic tackifying resins include alkylphenolic resins, xylene formaldehyde resins, resol phenolic resins, and novolak phenolic resins. The tackifier is preferably an alicyclic hydrocarbon or aromatic hydrocarbon resin.
[0083] The content of the tackifier in the adhesive layer 10 is not limited to a specific value. For example, in the adhesive layer 10, the content of the tackifier is, for example, 5 parts by mass or more, preferably 10 parts by mass or more, and more preferably 20 parts by mass or more, relative to 100 parts by mass of the rubber-based polymer of the matrix 10m. The content of the tackifier is, for example, 200 parts by mass or less, preferably 140 parts by mass or less, and more preferably 120 parts by mass or less, relative to 100 parts by mass of the rubber-based polymer of the matrix 10m.
[0084] The adhesive layer 10 may be formed as an acrylic pressure-sensitive adhesive layer. As the acrylic pressure-sensitive adhesive layer, for example, a known acrylic pressure-sensitive adhesive layer may be used.
[0085] Example
[0086] Hereinafter, the present invention will be described in more detail by way of examples, but the present invention is not limited to the following examples.
[0087] <Example 1>
[0088] Tufprene A, an SBS resin manufactured by Asahi Kasei Corporation, Archon M-115, a tackifier manufactured by Arakawa Chemical Co., Ltd., and heavy calcium carbonate manufactured by MARUO CALCIUM Co., Ltd. as a filler were kneaded in a mixing ratio of 100 parts by mass, 25 parts by mass, and 35 parts by mass, respectively, to obtain a mixture. The mixture was hot-pressed at 150° C. and 4 MPa to obtain a sheet of Example 1 having a thickness of 200 μm.
[0089] A laminate was obtained by placing a foam No. 6800 manufactured by Nitto Denko Corporation between two sheets of Example 1. The foam was an EPDM foam having a structure of independent cells and had a thickness of 10 mm. The laminate was heated in an oven at 140° C. while applying a pressure of 2 kPa to the two sheets of Example 1 and the foam. Thus, a sealant of Example 1 was obtained.
[0090] <Examples 2 to 5>
[0091] Sheets of Examples 2 to 5 were obtained in the same manner as in Example 1 except that the mixing ratios of the SBS resin, the tackifier, and the heavy calcium carbonate were changed as shown in Table 1A. Seals of Examples 2 to 5 were obtained in the same manner as in Example 1 except that the sheets of Examples 2 to 5 were used instead of the sheet of Example 1.
[0092] <Example 6>
[0093] SBS resin (1) Calprene 501 manufactured by Dynasol, SBS resin (2) Solprene 4302 manufactured by Dynasol, tackifier Piccotac 7590N manufactured by Eastman, heavy calcium carbonate manufactured by MARUO CALCIUM, and bentonite Claytone HT manufactured by BYK were kneaded in proportions of 50 parts by mass, 50 parts by mass, 100 parts by mass, 100 parts by mass, and 10 parts by mass, respectively, to obtain a mixture. Heavy calcium carbonate and bentonite are fillers. The mixture was hot pressed at 150° C. and 4 MPa to obtain a sheet of Example 6 having a thickness of 200 μm. The seal of Example 6 was obtained in the same manner as in Example 1, except that the sheet of Example 6 was used instead of the sheet of Example 1.
[0094] <Example 7>
[0095] A sheet of Example 7 was obtained in the same manner as in Example 1 except that heavy calcium carbonate was not added and the mixing ratio of the SBS resin and the tackifier was changed as shown in Table 1A. A seal of Example 7 was obtained in the same manner as in Example 1 except that the sheet of Example 7 was used instead of the sheet of Example 1.
[0096] <Example 8>
[0097] A sealing material of Example 8 was obtained in the same manner as in Example 2, except that an EPDM foam was disposed between the sheet of Example 2 and the substrate-free double-sided tape α composed of an acrylic pressure-sensitive adhesive layer. The thickness of the double-sided tape α was 70 μm.
[0098] <Example 9>
[0099] A sealing material of Example 9 was obtained in the same manner as in Example 8, except that EE-1000 manufactured by Nitto Denko Corporation was used as the EPDM foam instead of No. 6800. The foam had a structure of semi-closed and semi-open cells and a thickness of 10 mm.
[0100] <Example 10>
[0101] SBS resin D1155 manufactured by Kraton and tackifier Archon M-115 manufactured by Arakawa Chemical Industries were kneaded in a mixing ratio of 100 parts by mass and 40 parts by mass, respectively, to obtain a mixture. The mixture was hot-pressed under conditions of 150° C. and 4 MPa to obtain a sheet of Example 10 having a thickness of 200 μm. A sealing member of Example 10 was obtained in the same manner as in Example 1 except that the sheet of Example 10 was used instead of the sheet of Example 1.
[0102] <Example 11>
[0103] A sheet of Example 11 having a thickness of 200 μm was obtained in the same manner as in Example 10 except that the mixing ratio of the SBS resin and the tackifier was changed to 100 parts by mass and 60 parts by mass, respectively. A sealing material of Example 11 was obtained in the same manner as in Example 1 except that the sheet of Example 11 was used instead of the sheet of Example 1.
[0104] <Example 12>
[0105] A sheet of Example 12 having a thickness of 200 μm was obtained in the same manner as in Example 10 except that the mixing ratios of the SBS resin and the tackifier were changed to 100 parts by mass and 35 parts by mass, respectively.
[0106] A laminate was obtained by placing a foam No. 6800 manufactured by Nitto Denko Corporation between the sheet of Example 12 and a double-sided tape α without a substrate composed of an acrylic adhesive layer. The laminate was heated in an oven at 140° C. while applying a pressure of 2 kPa, so that the sheet of Example 12 and the double-sided tape α were bonded to the foam. Thus, a sealing member of Example 12 was obtained.
[0107] <Example 13>
[0108] A laminated body was obtained by placing a foam No. 6800 manufactured by Nitto Denko Corporation between the sheet of Example 12 and the double-sided tape β containing an acrylic adhesive layer. The laminated body was heated in an oven at 140° C. while applying a pressure of 2 kPa, so that the sheet of Example 12 and the double-sided tape β were bonded to the foamed body. Thus, a sealing member of Example 13 was obtained. The thickness of the double-sided tape β was 200 μm.
[0109] <Example 14>
[0110] SEBS resin G1657 manufactured by Kraton and tackifier Archon P-115 manufactured by Arakawa Chemical Industries were kneaded in a mixing ratio of 100 parts by mass and 35 parts by mass, respectively, to obtain a mixture. The mixture was hot-pressed under conditions of 150° C. and 4 MPa to obtain a sheet of Example 14 having a thickness of 200 μm. A seal of Example 14 was obtained in the same manner as in Example 1 except that the sheet of Example 14 was used instead of the sheet of Example 1.
[0111] <Example 15>
[0112] A sheet of Example 15 having a thickness of 200 μm was obtained in the same manner as in Example 14 except that the mixing ratio of the SEBS resin and the tackifier was changed to 100 parts by mass and 45 parts by mass, respectively. A sealing material of Example 15 was obtained in the same manner as in Example 1 except that the sheet of Example 1 was replaced with the sheet of Example 1.
[0113] <Example 16>
[0114] A sheet of Example 16 having a thickness of 200 μm was obtained in the same manner as in Example 14 except that the mixing ratio of the SEBS resin and the tackifier was changed to 100 parts by mass and 60 parts by mass, respectively. A sealing material of Example 16 was obtained in the same manner as in Example 1 except that the sheet of Example 1 was replaced with the sheet of Example 1.
[0115] <Example 17>
[0116] A sheet of Example 17 having a thickness of 200 μm was obtained in the same manner as in Example 14 except that the mixing ratio of the SEBS resin and the tackifier was changed to 100 parts by mass and 80 parts by mass, respectively. A sealing material of Example 17 was obtained in the same manner as in Example 1 except that the sheet of Example 1 was replaced with the sheet of Example 1.
[0117] <Example 18>
[0118] A laminate was obtained by placing a foam No. 6800 manufactured by Nitto Denko Corporation between the sheet of Example 15 and a double-sided tape α without a substrate composed of an acrylic adhesive layer. The laminate was heated in an oven at 140° C. while applying a pressure of 2 kPa, so that the sheet of Example 15 and the double-sided tape α were bonded to the foam. Thus, a sealing member of Example 18 was obtained.
[0119] <Example 19>
[0120] A laminated body was obtained by placing a foam No. 6800 manufactured by Nitto Denko Corporation between the sheet of Example 15 and the double-sided tape β containing an acrylic adhesive layer. The laminated body was heated in an oven at 140° C. while applying a pressure of 2 kPa, so that the sheet of Example 15 and the double-sided tape β were bonded to the foamed body. Thus, a sealing member of Example 19 was obtained.
[0121] <Comparative Example 1>
[0122] A sealing material of Comparative Example 1 was obtained in the same manner as in Example 1, except that an EPDM foam was disposed between the sheet and the double-sided tape α of Example 1. The thickness of the double-sided tape was 70 μm.
[0123] <Comparative Example 2>
[0124] The foam EE-1000 and the double-sided tape α were stacked to obtain a sealing material of Comparative Example 2 in which one main surface of the foam EE-1000 was exposed.
[0125] <Comparative Example 3>
[0126] EPDM foam EC-100 manufactured by Nitto Denko Corporation was placed between two sheets of double-sided tape α, and two sheets of double-sided tape α were bonded to both main surfaces of the foam to obtain a sealing member of Comparative Example 3. The foam had a structure of semi-closed and semi-open cells and a thickness of 10 mm.
[0127] <Comparative Example 4>
[0128] A sheet of Comparative Example 4 was obtained in the same manner as in Example 1 except that only SBS resin was used without adding a tackifier and a filler. A sealing material of Comparative Example 4 was obtained in the same manner as in Example 1 except that the sheet of Comparative Example 4 was used instead of the sheet of Example 1.
[0129] <90° peel adhesion>
[0130] The initial 90° peel adhesion F1 and F2 of the two main surfaces of the seal of each embodiment and each comparative example were measured according to JIS Z 0237:2022. As a test plate for pasting the seal, a SUS304 steel plate with a thickness of 1.5 mm was used. For this measurement, the sample made of the seal had a length of 100 mm and a width of 20 mm when viewed from above. When the seal was pasted on the test plate, a roller with a weight of 2 kg was reciprocated once along the length direction of the sample. In this measurement, the seal was peeled off at a time point of 30 minutes after the seal was pasted on the test plate. The test speed in this measurement was 300 mm / minute. The results are shown in Table 1A, Table 1B, and Table 2.
[0131] The 90° peeling strength F1 after one day of affixing the sealant to the test plate was measured in the same manner as the 90° peeling strength F1 and F2. 一天 and F2 一天 The results are shown in Table 1A, Table 1B, and Table 2.
[0132] <Tear strength of foam>
[0133] According to JIS K 6252-1:2015, uncut angular test pieces were made from EPDM foam No. 6800, EE-1000, and EC-100, respectively. The thickness of the test piece was 10 mm. According to JIS K 6252-1:2015, the test piece was torn at a test speed of 500 mm / min, and the tear strength T of each EPDM foam was measured. The tear strength T was determined by converting the value obtained by dividing the maximum load [N] measured when tearing the test piece by the thickness of the test piece into the unit of [N / 20 mm]. The results are shown in Table 1A, Table 1B, and Table 2.
[0134] <Viscosity value>
[0135] One main surface of the seal of each embodiment and each comparative example is defined as the first surface, and the other main surface is defined as the second surface. According to a part of ASTM D2979:2016, a probe viscosity test was performed on the second surface of each seal. In this test, the test device Autograph AG-I manufactured by Shimadzu Corporation was used. In addition, an aluminum cylindrical rod was used as a probe. The probe has a circular end surface with a diameter of 5 mm. Each seal was cut into a square shape with a length of 30 mm on one side when viewed from above, and a sample for the probe viscosity test was obtained. Each sample was arranged in the test device in such a way that the second surface of the seal faces the probe, and the probe with a circular end surface with a diameter of 5 mm was brought close to the sample at a speed of 10 mm / min until a force of 0.25 N was applied. After that, the position of the probe was fixed for 1 second, and the probe was pulled away from the second surface of the sample at a speed of 100 mm / min. The maximum value of the force acting on the probe when pulling the probe away from the second surface of the sample was divided by the area of the end surface of the probe to determine the viscosity value V. Tack The results are shown in Table 1A, Table 1B, and Table 2.
[0136] A portion with a thickness of 200 μm including the second surface was cut out in the thickness direction of the seal of each embodiment and each comparative example, and a dumbbell shape No. 1 was cut from the portion according to JIS K6251:2017 to produce a test piece for measuring the tensile modulus. Using the test piece, a tensile test was carried out under the conditions of a distance between markings of 40 mm and a test speed of 1000 mm / min according to JIS K6251:2017. The strain range of 2% to 10% of the stress-strain curve obtained by the test was linearly approximated by the least squares method, and the slope of the approximate straight line was determined as the tensile modulus. The results are shown in Table 1A, Table 1B, and Table 2.
[0137] <Evaluation of adhesiveness using a roller>
[0138] The seals of each embodiment and each comparative example were cut into pieces having a width of 10 mm and a length of 150 mm, and samples for evaluating the adhesion using a roller were prepared. The samples were arranged on the SUS304 steel plate in such a way that the first surface of each seal was in contact with the surface of a SUS304 steel plate having a thickness of 1.5 mm, and a rubber hand roller was rolled on the second surface of each seal to adhere the sample to the SUS304 steel plate. The roller portion of the hand roller had a diameter of 24 mm and a width of 30 mm. The rotation speed (circumferential speed) of the roller portion was adjusted to 200 mm / min. The adhesion of each seal was evaluated according to the following benchmarks. The results are shown in Table 1A, Table 1B, and Table 2.
[0139] AA: The seal does not get tangled around the roller and can be easily attached.
[0140] A: The seal will not be entangled on the roller and can be pasted.
[0141] B: The sealant is not entangled on the roller and can be attached, but the sealant is not easily peeled off from the roller.
[0142] C: The seal will be entangled on the roller and cannot be attached.
[0143] <Evaluation of water-stopping properties>
[0144] The seals of each embodiment and each comparative example were cut into a ring shape with an inner diameter of 50 mm and an outer diameter of 70 mm to produce a test piece for IPX7 test. The test piece was placed between two acrylic plates, and a spacer was placed around the test piece between the two acrylic plates so that the test piece was fixed in a state of 50% compression deformation in the thickness direction of the acrylic plate. The acrylic plate was ACRYLITE EX manufactured by Mitsubishi Chemical Co., Ltd. and had a thickness of 10 mm. In this way, a sample for IPX7 test was produced. The sample was immersed in a water tank filled with water to a height of 1 m, and the sample was taken out after a specified time, and the water-stopping property of each sample was evaluated according to the following criteria. The results are shown in Table 1A, Table 1B, and Table 2.
[0145] A: After the sample is immersed in the water tank for 24 hours, there is no water leakage inside the ring-shaped test piece.
[0146] B: After the sample was immersed in the water tank for 24 hours, water leaked from the inside of the donut-shaped test piece. However, after the sample was immersed in the water tank for 30 minutes, there was no water leak from the inside of the donut-shaped test piece.
[0147] C: After the sample was immersed in the water tank for 30 minutes, water leaked from the inside of the ring-shaped test piece.
[0148] The seals of each embodiment and each comparative example were cut into a ring shape with an inner diameter of 50 mm and an outer diameter of 70 mm to produce a test piece for IPX9K test. The test piece was arranged between two polycarbonate plates, and a spacer was arranged around the test piece between the two polycarbonate plates so that the test piece was fixed in a state of 50% compression deformation in the thickness direction of the acrylic plate. The polycarbonate plate was PC1600 manufactured by TAKIRON-CI and had a thickness of 10 mm. In this way, a sample for IPX9K test was produced. In a state where the sample was arranged in a horizontal manner with two polycarbonate plates, water was sprayed on the sample for 30 seconds from each direction at an angle of 0°, 30°, 60°, and 90° relative to the horizontal plane under the conditions of a temperature of 80°C, a water pressure of 8MPa, and a water volume of 14L / min, and a total of 2 minutes of water was sprayed. The distance between the spray port of the nozzle for spraying water and the outer peripheral end of the test piece in the sample was adjusted to 10cm. At an angle of 0°, the nozzle's jet port was located at approximately the same height as the test piece, and at angles of 30°, 60°, and 90°, the nozzle's jet port was located at a position higher than the sample. The water stopping properties of each sample were evaluated based on the following criteria. The results are shown in Table 1A and Table 2.
[0149] A: There is no water leakage inside the ring-shaped test piece.
[0150] C: Water leaked from the inside of the ring-shaped test piece.
[0151] As shown in Table 1A, Table 1B, and Table 2, the seals of each embodiment have good adhesion using a roller and good water-stopping properties. On the other hand, the seals of Comparative Examples 1 and 3 have difficulty in adhesion using a roller. Although the seals of Comparative Examples 2 and 4 can be pasted using a roller, it is difficult to say that they have high water-stopping properties. It is understandable that from the perspective of pasting the seal while pressing the seal with a roller and water-stopping properties, it is advantageous for the sealing member to satisfy the conditions of F1≥F2, T>F2, F1≥0.3N / 20mm, and F2≥0.3N / 20mm.
[0152] The first side of the present invention provides a seal, comprising: a first surface; and a second surface facing a direction opposite to the direction facing the first surface, the seal satisfying the conditions of F1≥F2, T>F2, F1≥0.3N / 20mm, and F2≥0.3N / 20mm, wherein F1 and F2 are respectively the 90° peel adhesion [N / 20mm] measured by peeling off the first surface and the second surface in accordance with Japanese Industrial Standard (JIS) Z 0237:2022; wherein T is the tear strength [N / 20mm] measured in accordance with JIS K6252-1:2015 using an uncut angular test piece made from a portion of the seal away from the first surface and the second surface.
[0153] The second aspect of the present invention provides a sealing member, wherein in the first aspect, the second surface has a 20N / cm 2 The following viscosity values are determined by dividing the maximum value of the force acting on the probe when the end face of a probe having a circular end face with a diameter of 5 mm is pressed against the second face with a force of 0.25 N for 1 second and then the probe is pulled away from the second face at a speed of 100 mm / min by the area of the end face.
[0154] A third aspect of the present invention provides a sealing member, wherein in the first aspect or the second aspect, the sealing member includes a foam.
[0155] A fourth aspect of the present invention provides a sealing member, wherein in the third aspect, the foam has a closed cell structure.
[0156] A fifth aspect of the present invention provides a sealing member, wherein in any one of the first to fourth aspects, the sealing member includes at least two layers.
[0157] A sixth aspect of the present invention provides a sealing member including, on any one of the first to fifth aspects, an adhesive layer forming at least one surface selected from the group consisting of the first surface and the second surface.
[0158] A seventh aspect of the present invention provides a sealing member, wherein in the sixth aspect, the adhesive layer contains a filler.
[0159] An eighth aspect of the present invention provides a sealing member wherein, in any one of the first to seventh aspects, a layer including the second surface or a portion having a thickness of 200 μm from the second surface has a tensile elastic modulus of 2 MPa or more.
[0160] A ninth aspect of the present invention provides a sealing member, wherein in any one of the first to eighth aspects, F1 一天 and F2 一天5N / 20mm or more, F1 一天 The 90° peeling strength is measured according to JIS Z 0237:2022, where the seal is attached to a test plate with the first surfaces in contact, and then the seal is peeled off after one day. F2 一天 The 90° peeling adhesive strength is measured in accordance with JIS Z 0237:2022 by attaching the sealing material to a test plate with the second surface in contact, and then peeling off the sealing material after one day.
[0161] [Table 1A]
[0162]
[0163] [Table 1B]
[0164]
[0165] [Table 2]
[0166]
Claims
1. A seal, wherein: The sealing member comprises: a first surface; and a second side facing in a direction opposite to the direction facing the first side, The seal meets the conditions of F1≥F2, T>F2, F1≥0.3N / 20mm, and F2≥0.3N / 20mm, In the above conditions, F1 and F2 are the 90° peeling adhesive strengths measured by peeling off the first surface and the second surface according to Japanese Industrial Standard JIS Z 0237:2022, and the unit is N / 20 mm. In the above conditions, T is the tear strength measured in accordance with JIS K 6252-1:2015 using an uncut angled test piece made from a portion of the seal member that is away from the first surface and the second surface, and the unit is N / 20 mm.
2. The seal according to claim 1, wherein: The second surface has a 20N / cm 2 The following viscosity values, The viscosity value is determined by dividing the maximum value of the force acting on the probe when the end face of a probe having a circular end face with a diameter of 5 mm is pressed against the second face with a force of 0.25 N for 1 second and then the probe is pulled away from the second face at a speed of 100 mm / min by the area of the end face.
3. The seal according to claim 1, wherein: The sealing material includes a foamed body.
4. The seal according to claim 3, wherein: The foam has a closed cell structure.
5. The seal according to claim 1, wherein: The seal has at least two layers.
6. The seal according to claim 1, wherein: The sealing material includes an adhesive layer forming at least one surface selected from the group consisting of the first surface and the second surface.
7. The seal according to claim 6, wherein: The bonding layer contains a filler.
8. The seal according to claim 1, wherein: The layer including the second surface or a portion having a thickness of 200 μm from the second surface has a tensile elastic modulus of 2 MPa or more.
9. The seal according to claim 1, wherein: F1 一天 and F2 一天 5N / 20mm or more, F1 一天 The 90° peeling adhesive strength is measured according to JIS Z 0237:2022, by attaching the seal to a test plate with the first surfaces in contact, and then peeling off the seal after one day. F2 一天 The 90° peeling adhesive strength is measured in accordance with JIS Z 0237:2022 by attaching the sealing material to a test plate in a state where the second surface is in contact, and then peeling off the sealing material after one day.
Citation Information
Patent Citations
Water-stopping sealing material
JP1998077463A